1981
DOI: 10.1083/jcb.88.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Different polypeptides form the intermediate filaments in bovine hoof and esophageal epithelium and in aortic endothelium.

Abstract: Polypeptides that form 10-nm filaments in vitro were isolated from three different bovine tissues: the viable portion of the hoof epithelium, the epithelium of the esophagus, and cultured endothelial cells derived from aorta. The seven polypeptides from hoof, the two from esophagus, and the one from endothelial cells were different with respect to mobility in SDS polyacrylamide gels and/or limited proteolytic digestion. Peptide maps of the different filament-forming polypeptides (FFP's) showed that none of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
2

Year Published

1982
1982
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 25 publications
1
25
0
2
Order By: Relevance
“…Peptide mapping has established homologies between vimentin and desmin (21). Likewise, immunological and biochemical studies revealed extensive crossreactivity within a given class of polypeptides, keratins (22,23 Similar to the findings, reported here, with the monoclonal IgM antibody produced by patient GON, the availability of hybridoma-derived monoclonal antibodies will undoubtedly uncover new crossreactivities within the family of structurally and functionally related IF proteins. Recently, a mouse hybridoma antibody has been shown to react with an antigenic determinant shared by the five classes ofIF (25).…”
supporting
confidence: 59%
“…Peptide mapping has established homologies between vimentin and desmin (21). Likewise, immunological and biochemical studies revealed extensive crossreactivity within a given class of polypeptides, keratins (22,23 Similar to the findings, reported here, with the monoclonal IgM antibody produced by patient GON, the availability of hybridoma-derived monoclonal antibodies will undoubtedly uncover new crossreactivities within the family of structurally and functionally related IF proteins. Recently, a mouse hybridoma antibody has been shown to react with an antigenic determinant shared by the five classes ofIF (25).…”
supporting
confidence: 59%
“…Differences in the polypeptide complexity of the keratins produced by various epithelial cells have been demonstrated both for the intact tissue (10,11,15,23,24,43) and for cells grown in culture (9,16,40,41,46). However, it was not determined previously whether this variation in keratins with cell type represents tissue-specific differences in the synthesis of keratin mRNAs or, alternatively, posttranslational processing or modification of a defined set of keratin polypeptides.…”
Section: Discussionmentioning
confidence: 96%
“…The large keratins are abundant only in differentiating epidermal cells and are probably associated with stratum corneum formation (7,13,15,35). The smaller keratins are present in conjunctival cells (16,41), the intestinal epithelium (10), mesothelial cells (46), and many simple and glandular epithelia (24), but they are not prominent in epidermal cells, esophageal cells, or epithelial cells of the oral cavity (10,15,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical data indicate that the polypeptide composition of keratin filaments varies depending on epithelial cell type (12,14,15,18,21,26,39), cellular growth environment (3,12,20,22,23,32,53,60), histological differentiation stage (6, 9, 2 l, 49, 5 l, 56, 66, 67, 70), and embryonic development period (4, 11). It is therefore not surprising that many keratin species have been described in the literature.…”
mentioning
confidence: 99%